Clinician and patient attitudes toward use of organs from hepatitis C viremic donors and their impact on acceptance: A contemporary review. Issue 12 (30th October 2021) - Fleetwood, Vidya A.; Maher, Kennan; Satish, Sangeeta; Varma, C. Rathna; Nazzal, Mustafa; Randall, Henry; Al‐Adra, David P.; Caliskan, Yasar; Bastani, Bahar; Rub, Fadee Abu Al; Lentine, Krista L.
Abstract: Background: The use of Hepatitis C (HCV) NAT positive allografts remains unusual and is clustered at few centers. We conducted a contemporary literature review to assess whether patient and clinician attitudes toward viremic organs impact acceptance. Methods: Databases including PubMed, MEDLINE, and SCOPUS databases were reviewed to identify studies focused on evaluating patient and provider perceptions of HCV NAT positive organ use within the DAA era (January 2015–April 2021). Search included MeSH terms related to Hepatitis C, transplantation, and patient and clinician attitudes. Two investigators extracted study characteristics including information on willingness to accept viremic organs, HCV‐specific outcomes knowledge, HCV‐specific concerns, and factors that contributed to acceptance or non‐acceptance. Results: Eight studies met all inclusion criteria. These included three pretransplant patient‐directed studies, two post‐transplant patient‐directed studies, one pre‐ and post‐transplant patient‐directed study, and two clinician‐directed studies. Common themes identified were concerns regarding HCV cure rates, viremic organ quality, DAA cost, stigma, and the possibility of HCV transmission to household members. The perception of decreased waitlist time was associated with viremic organ acceptance. Physician trust played a mixed role in acceptance patterns. Conclusions: Knowledge of high cure rates, shorter waitlist times, and higher organ quality appear to have the highest impact on organ acceptance.